“Library and Information Science” Literature in Web of Science: What a Decade Tells Us About Scholarly Collaboration in the Field (2007-2016) - Thompson, Kim M. (2020)
Ensuring access to published research is increasingly important for demonstrating research impact, supporting wide readership, creating interest in collaboration, and making way for funding opportunities. This article provides a bibliometric analysis of publications from 2007-2016 in the Web of Science (WOS) database to update understanding of recent international library science research as a means of discussing research impact and scientific collaboration. The methodology is a descriptive analysis of publications retrieved from the WOS database using keywords “library science” and WOS-generated subject descriptor “Information Science & Library Science.”  Analysis focused on descriptive data related to our research questions including representation of countries, languages, and journals. The findings reveal that most publications are published by researchers with institutional affiliations in the United States and in English. Library and information science research continues to be strong in collaboration, but international and interdisciplinary collaborations are still low in this sample. The dataset reflects that co- and multi-authored publications have the highest WOS citation counts, reinforcing the value of scholarly collaboration. This research provides a baseline to chart future growth in Library Science research publications and collaborations.